Global burden of head and neck cancer from 1990 to 2021: A comprehensive analysis and projections to 2030 based on the global burden of disease study 2021 - Muling Deng; Yuhao Lin; Linghui Yan; Zhaodong Fei; Chuanben Chen; Jianming Ding (PLoS ONE, 2025)
Background Head and neck cancer (HNC) is a significant global health concern with rising incidence and mortality in certain regions. This study aimed to evaluate the global burden and temporal trends of HNC from 1990 to 2021 and to project its future burden through 2030. Methods Data were obtained from the Global Burden of Disease (GBD) 2021 study. Joinpoint regression was used to assess temporal trends in age-standardized incidence rates (ASIR), age-standardized death rates (ASDR), and disability-adjusted life years (DALYs). Age–period–cohort (APC) and Bayesian APC (BAPC) models were applied to evaluate age, period, and cohort effects and to project future trends. Decomposition analysis was conducted to explore the contributions of population aging, growth, and epidemiological changes. Results In 2021, there were 792,280 new HNC cases and 424,066 deaths globally. Age-standardized incidence rates remained stable, while death rates and DALYs significantly declined. Incidence rose notably in East Asia, whereas mortality and DALYs increased substantially in Oceania. Gender differences were evident, with higher burdens in males, although female incidence rates recently increased. Aging and population growth were key contributors to the rising burden. Projections suggest a notable increase in female incidence and continued decline in male DALYs by 2030. Among HNC subtypes, lip and oral cavity cancers had the highest burden, whereas other pharyngeal cancers showed increasing incidence trends. Conclusions Despite overall declines in mortality and disease burden, the global incidence of HNC remains substantial. Targeted interventions—such as tobacco and alcohol control and widespread HPV vaccination—are essential to mitigate the future burden of HNC.